2016
DOI: 10.1097/pep.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Enjoyment of a Swimming Intervention for Youth With Cerebral Palsy

Abstract: We recommend a swimming program for youth with CP to complement a physical therapy program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 23 publications
(34 reference statements)
4
48
1
3
Order By: Relevance
“…There is evidence that positive feelings and high levels of enjoyment and satisfaction during physical activity are associated with increased levels of exercise adherence . Our results are in agreement with Declerck et al and McNamara et al studies who reported high levels of enjoyment following a swimming training programme in children and adolescents with cerebral palsy and in elderly people with chronic obstructive pulmonary disease, respectively. We, also, found that the level of enjoyment did not differ between boys and girls which is in line with a previous study in high school students …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There is evidence that positive feelings and high levels of enjoyment and satisfaction during physical activity are associated with increased levels of exercise adherence . Our results are in agreement with Declerck et al and McNamara et al studies who reported high levels of enjoyment following a swimming training programme in children and adolescents with cerebral palsy and in elderly people with chronic obstructive pulmonary disease, respectively. We, also, found that the level of enjoyment did not differ between boys and girls which is in line with a previous study in high school students …”
Section: Discussionsupporting
confidence: 93%
“…This notion has been strengthened by the results of the present and a previous study which reported that the incorporation of experienced‐based (practical application) learning activities may improve aquaticity (in the present study) and water safety skills in healthy primary school students. Furthermore, the results of this study are in line with previous studies that examined the effects of specialised swimming training programmes (10 weeks) and reported an increase in swimming‐aquatic skills in diseased (autism, cerebral palsy) children and adolescents …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Su sporlarının SP'li çocuklar için daha yararlı olacağını ve diğer egzersizler içinde cesaret verici olacağını belirtmişlerdir 35 . Derclerck ve arkadaşları 7-17 yaş arası SP'li bireylere 12 haftalık su egzersiz programı uygulanmış ve yüzme egzersizinin hareket kabiliyetini geliştirdiğini bulmuşlardır 36 . Fragala-Pinkham ve arkadaşları ise 6-15 yaş arası SP'li çocuklara 14 haftalık su içi egzersiz programı uygulanmasının, motor kabiliyet ve yürüme yeteneğinde olumlu etkisi olduğunu göstermişlerdir 37,38 .…”
Section: Yüzme Ve Serebral Palsiunclassified